BEGÔNIA RIEGER: NOVO HOSPEDEIRO DE Aphelenchoides ritzemabosi NO ESTADO DE SÃO PAULO - Rossi, Carlos Eduardo; Monteiro, Ailton Rocha (REVISTA DE AGRICULTURA, 2015)
BEGÔNIA RIEGER: NOVO HOSPEDEIRO DE Aphelenchoides ritzemabosi NO ESTADO DE SÃO PAULO